An account of the second phase of the conquest of Navarre in 1512 - Monteano Sorbet, Peio J. (Huarte de San Juan. Geografía e Historia, 2021)
In mid-December 1512, Ferdinand of Aragon sent through his ambassador a letter to his ally, Emperor Maximilian I of Austria. He related the victory of his army in Navarre. This letter precises and confirms the major military movements against the franco-navarre army in fall 1512. The main result was the expulsion of the navarre ambassador, Salvador de Berrio, from the imperial court.